Effect of water stress on the growth, physiological response and antioxidative gene expression of grafted sweet pepper plants - Sae-Tang, Wannida; Nawata, Eiji (Agriculture and Natural Resources, 2019)
Grafting has been introduced as an alternative technique to alleviate damage to horticultural crops from water stress and to improve tolerance. In this study, non-grafted (FT) and grafted sweet pepper ‘Fushimiamanaga togarashi’ onto chili pepper ‘Huaysiiton’ (FT/HS) and ‘Shima togarashi’ (FT/ST) plants were grown under drought conditions. The results indicated that water stress had a considerable influence on both non-grafted and grafted plants. The growth of sweet peppers decreased due to water stress, with the FT/ST plants having a reduced decrease compared to plants with sufficient watering. Consequently, these grafted plants had the smallest yield reduction caused by water deficit. However, under well-watered conditions, non-grafted plants had greater total yields than grafted plants. The photosynthetic rates, transpiration rates and carbon dioxide intercellular space concentrations also declined significantly due to drought. The grafted plants were able to maintain photosynthesis under water stress conditions to some extent. The leaf water and leaf osmotic potentials declined substantially under water stress conditions, with the FT/ST plants having the lowest leaf osmotic potential, even though the leaf water potential remained rather high. The expression of antioxidative genes relating to CuZnSOD, MnSOD, CAT and APX were upregulated at transcriptional levels under water stress conditions, especially in FT/ST. The Shima togarashi chili pepper may have potential to be used as a vigorous rootstock under water stress conditions based on physiological adaptation and antioxidative gene expression, although it produced a lower yield than non-grafted plants under non-stressed conditions.